The Cooling-Off Period Under the International Investment Law Regime in the Indonesian Regulations Context - Allagan, Tiurma M. Pitta; Simbolon, Putu George Matthew (Journal of Indonesian Legal Studies, 2024)
This article seeks to find methods for preventing the chilling effect of International Investment Law (“IIL”), according to the Indonesian legal system. The IIL has been known as one of the controversial legal regimes in international law, due to its main issue to balance the right of foreign investors and the sovereignty of the host state. From the host state’s point of view, an international arbitration tribunal award in favor of the foreign investors may cause a chilling effect on its right to regulate an investment measure. Since Indonesia is a country that is currently experiencing this effect, the article herein provides three discussions on how the chilling effect can be prevented. In providing these discussions, this article applies the doctrinal approach by taking into account the cases in hand, particularly where Indonesia is one of the parties. The first discussion provides explanations concerning the Tecmed v. Mexico case, which reflects how the absence of domestic law concerning cooling-off period may damage a state’s sovereignty. This discussion also provides findings in Amco v. Indonesia and Oleovest v. Indonesia, which shall be considered as cases where Indonesia applied its cooling-off period, despite its defeat in the Amco’s Tribunal. Furthermore, the second discussion explains how the cooling-off period and the exhaustion of local remedies are interconnected. This discussion shows the weakness within the Indonesian legal system and an example of the Indonesian government’s BITs, which consist of a cooling-off period, despite not transposed to its national law. Last but not least, the third discussion explores how a mediation and administrative court shall be utilized by Indonesia as a cooling-off period mechanism. This discussion also consists of recommendations on how Indonesia’s national investment law shall be amended in preventing the IIL chilling effect.